2020
DOI: 10.1002/lary.28713
|View full text |Cite
|
Sign up to set email alerts
|

Age Is Associated With Pain Experience and Opioid Use After Head and Neck Free Flap Reconstruction

Abstract: Objectives To describe pain experience and opioid use after major head and neck reconstructive surgery. Study Design Retrospective cohort study. Methods Patients undergoing major head and neck surgery with microvascular free tissue transfer (free flaps) at a tertiary academic center were included. Pain scores (0–10) and demographic and clinical data were ascertained from medical records. Discharge opioid prescriptions and refills obtained within 30 days were recorded. Patient characteristics were compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Like in the present study, older age has been consistently shown to be associated with decreased use of opioids in patients with head and neck cancer 10,27,28 . This may be due decreased pain sensitivity in elderly populations 29 . This is the first study to report an association of having dependent children with opioid use and this may warrant further study.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Like in the present study, older age has been consistently shown to be associated with decreased use of opioids in patients with head and neck cancer 10,27,28 . This may be due decreased pain sensitivity in elderly populations 29 . This is the first study to report an association of having dependent children with opioid use and this may warrant further study.…”
Section: Discussionsupporting
confidence: 68%
“…10,27,28 This may be due decreased pain sensitivity in elderly populations. 29 This is the first study to report an association of having dependent children with opioid use and this may warrant further study. In addition to these socioeconomic factors, pain score during radiation therapy was associated with opioid use.…”
Section: Characteristicmentioning
confidence: 79%
“…Free tissue reconstruction is the gold-standard for wounds with exposed bone devoid of periosteum, but is associated with increased donor-site morbidity, cost, and postoperative pain. [11][12][13] These risks are magnified in the IDU population where ongoing drug use or relapse and poor adherence to postoperative care may increase the risk of complications and failure. 3,12 Less complex options such as skin grafting or locoregional flaps may be contraindicated secondary to debridement of the periosteum, surrounding soft-tissue fibrosis, and persistent infection.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] These risks are magnified in the IDU population where ongoing drug use or relapse and poor adherence to postoperative care may increase the risk of complications and failure. 3,12 Less complex options such as skin grafting or locoregional flaps may be contraindicated secondary to debridement of the periosteum, surrounding soft-tissue fibrosis, and persistent infection. 2 NPD can also be utilized to stimulate granulation for skin grafting; however, the size of the defect, possible persistent infection, and need for prolonged treatment may cause problems with this approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation